Clinical application of OCTA in diabetic retinopathy - Cheng Qin (Guoji Yanke Zazhi, 2020)
Diabetic retinopathy is the most common disease of microvascular diseases caused by diabetes. It is harmful to vision in the late stage. If not treated in time, it can cause blindness. The diagnosis, treatment and follow-up of diabetic retinopathy were mainly based on fundus fluorescein angiography. There are some limitations in the clinical application because of the side effects of its operation, such as invasive, allergic and adverse reactions. Recently, optical coherence tomography has become more and more popular among ophthalmologists for its noninvasive, rapid and high resolution fundus angiography. It cannot only display the choroidal vascular network information in layers, but also quantitatively analyze the changes of blood flow in the macular region. For the first time, the blood flow analysis of optic disc and macular area in vivo has reached the level of tissue anatomy. It has wide application prospect and is more and more favored by ophthalmologists. In this paper, the clinical application of octa in diabetic retinopathy was reviewed.